Two new cadmium(II) coordination polymers based on bis(1, 2, 4‐triazol‐1‐yl)alkane ligands and pyrazine‐2, 3‐dicarboxylic acid. Issue 10 (1st October 2015) - Xia, Jun; Gong, Xiao‐Lin; Fan, Xing
<x xml:space="preserve">Abstract</x> Assemblies of pyrazine‐2, 3‐dicarboxylic acid and CdII in the presence of bis(1, 2, 4‐triazol‐1‐yl)butane or bis(1, 2, 4‐triazol‐1‐yl)ethane under ambient conditions yielded two new coordination polymers, namely poly[[tetraaqua[μ2‐1, 4‐bis(1, 2, 4‐triazol‐1‐yl)butane‐κ2N4:N4′]bis(μ2‐pyrazine‐2, 3‐dicarboxylato‐κ3N1, O2:O3)dicadmium(II)] dihydrate], [Cd2(C6H2N2O4)2(C8H12N6)(H2O)4]·2H2On, (I), and poly[[diaqua[μ2‐1, 2‐bis(1, 2, 4‐triazol‐1‐yl)ethane‐κ2N4:N4′]bis(μ3‐pyrazine‐2, 3‐dicarboxylato‐κ4N1, O2:O3:O3′)dicadmium(II)] dihydrate], [Cd2(C6H2N2O4)2(C6H8N6)(H2O)2]·2H2On, (II). Complex (I) displays an interesting two‐dimensional wave‐like structure and forms a distinct extended three‐dimensional supramolecular structure with the help of O—H...N and O—H...O hydrogen bonds. Complex (II) has a three‐dimensional framework structure in which hydrogen bonds of the O—H...N and O—H...O types are found.